Factors associated with adherence to self-isolation and lockdown measures in the UK: a cross-sectional survey. (October 2020) - Smith, L.E.; Amlȏt, R.; Lambert, H.; Oliver, I.; Robin, C.; Yardley, L.; Rubin, G.J.
Abstract: Objectives: To investigate factors associated with adherence to self-isolation and lockdown measures due to COVID-19 in the UK. Study design: Online cross-sectional survey. Methods: Data were collected between 6th and 7th May 2020. A total of 2240 participants living in the UK aged 18 years or older were recruited from YouGov's online research panel. Results: A total of 217 people (9.7%) reported that they or someone in their household had symptoms of COVID-19 (cough or high temperature/fever) in the last 7 days. Of these people, 75.1% had left the home in the last 24 h (defined as non-adherent). Men were more likely to be non-adherent, as were people who were less worried about COVID-19, and who perceived a smaller risk of catching COVID-19. Adherence was associated with having received help from someone outside your household. Results should be taken with caution as there was no evidence for associations when controlling for multiple analyses. Of people reporting no symptoms in the household, 24.5% had gone out shopping for non-essentials in the last week (defined as non-adherent). Factors associated with non-adherence and with a higher total number of outings in the last week included decreased perceived effectiveness of government 'lockdown' measures, decreased perceived severity of COVID-19 and decreased estimates of how many other people were following lockdown rules. Having received help was associated with better adherence. Conclusions: Adherence to self-isolation is poor. As we move into a new phase of contact tracing and self-isolation, it is essential that adherence is improved. Communications should aim to increase knowledge about actions to take when symptomatic or if you have been in contact with a possible COVID-19 case. They should also emphasise the risk of catching and spreading COVID-19 when out and about and the effectiveness of preventative measures. Using volunteer networks effectively to support people in isolation may promote adherence. Highlights: 75% of those with household COVID-19 symptoms had left home in the last 24 h. Total outings and shopping for non-essentials indicated non-adherence to lockdown. Decreased perceived effectiveness of lockdown measures was linked to non-adherence. Non-adherence was also linked with decreased perceived severity of COVID-19. Perceived social norms were associated with adherence to lockdown measures.